The Diver - Mayo, E. L. (Book collections on Project MUSE., 1947)
The Diver was first published in 1947. Although this is the first published collection of the poetry of E.L. Mayo, thirty poems in this volume were published previously in such magazines as Poetry and Partisan Review.